Burden of Noise Induced Hearing Loss among Manufacturing Industrial Workers in Malaysia - Noraita TAHIR; Syed Mohamed ALJUNID; Jamal Hisham HASHIM; Jaseema BEGUM (Tehran University of Medical Sciences, 2015)
Background: Noise induced hearing loss (NIHL) is the highest reported occupational disease among industrial workers but there is scarcity of data on disease burden in Malaysia. This study estimated the risks and burden of NIHL in manufacturing industries in Malaysia. Methods: This cross-sectional industrial survey was conducted by interviewing OSH practitioners at 26 industries categorized as food, tobacco, textile, wearing apparel, wood products except furniture, paper, refined petroleum, chemicals, non-metallic mineral, basic metal, fabricated metal, motor vehicle parts. The catchment population is imputed based on stratified sampling design involving 60% of workers diagnosed with NIHL. Results: A total of 18 industries exposed to noise level of 86-90dBA and 8 industries at more than 91dBA were identified. All industries provide regular awareness training and hearing protection device to their workers but none of them implement attenuation, majority of them (81%) conduct onsite audiometric test annually. In overall, the risk of NIHL and incidence per 100,000 manufacturing workers projected is 8% (139 new cases), the highest risk and incidence is 32% (26) in motor vehicle parts industry; followed by 23% (1140 new cases) in tobacco industry and 23% (269 new cases) in fabricated metal industry. Male workers (89%) were exposed to a greater risk compared to female (11%). It was estimated that 103,000 workers were potentially affected by NIHL in Malaysia. Conclusion: NIHL is a major burden among industrial workers in Malaysia. Implementation of effective hearing conservation program and self-enforcement of noise regulations by the employer could potentially reduce the burden.   Keywords: Noise, Hearing loss, Manufacturing, Malaysia